Digital Bridges or Digital Divides? The Impact of Innovation Capabilities on Digitally Deliverable Service Export - Dunel Rajkumar; Shuquan He (European Scientific Journal, ESJ, 2026)
This study investigates the differentiated impact of innovation capabilities on Information and Communication Technology (ICT) service exports through a comparative macroeconomic analysis of China and India from 2000 to 2024. As digital services increasingly drive global trade, understanding the distinct growth pathways of emerging giants is essential for targeted policy formulation. Utilising an Autoregressive Distributed Lag Error Correction Model (ARDL-ECM), this research examines long-term cointegration relationships and short-term dynamic adjustments. We model ICT export volume against resident patent applications, controlling for real exchange rates, digital infrastructure, and human capital. Findings reveal country-specific trajectories: China’s expansion relies heavily on long-term accumulation of digital infrastructure and human capital, with technical innovation showing limited direct impact. On the other hand, long-term innovation capability and exchange rate competitiveness significantly drive India’s export performance. Ultimately, the translation of innovation into trade competitiveness is non-uniform, requiring policymakers to tailor strategies to specific developmental stages.